(untitled) (Journal of the College of Basic Education, 2026)
The importance of this research lies in its contribution to establishing a scientific link between the results of motor abilities tests and the performance level of certain holds among wrestling at a critical age. It provides coaches with objective indicators that help them select appropriate exercises to develop the most impactful motor abilities for skill performance. The research problem is that the lack of scientific studies clearly linking motor abilities tests to the types of holds used by wrestling at this age leads to a lack of clarity in training priorities for coaches. The limited information on the relationship between basic motor abilities and the level of hold execution makes training programs less precise and effective, and may hinder the optimal development of the wrestling’ skills. The research aimed to: 1- Identify the level of performance in certain motor skills and grip tests for wrestling aged 12-14 years.-2- Identify the correlation between the results of certain motor skills tests and specific types of grips for wrestling aged 12-14 years. The researcher used a descriptive survey methodology. The research population consisted of wrestling aged 12-14 years. After administering the tests, the most important conclusions were: 1- The results of the motor skills tests and the assessment of grip performance, based on the obtained results, indicate that the sample’s level is good according to the maximum scores of the tests used, especially in grip performance. 2- There is a strong relationship between motor skills and grip performance in freestyle wrestling for the research sample aged 12-14 years. The most important recommendation was the necessity of focusing on motor skills due to their importance in improving grip performance, as demonstrated by the obtained results.